Direct AFM-based nanoscale mapping and tomography of open-circuit voltages for photovoltaics - Atamanuk, Katherine; Luria, Justin; Huey, Bryan D. (Beilstein Journal of Nanotechnology, 2018)
The nanoscale optoelectronic properties of materials can be especially important for polycrystalline photovoltaics including many sensor and solar cell designs. For thin film solar cells such as CdTe, the open-circuit voltage and short-circuit current are especially critical performance indicators, often varying between and even within individual grains. A new method for directly mapping the open-circuit voltage leverages photo-conducting AFM, along with an additional proportional-integral-derivative feedback loop configured to maintain open-circuit conditions while scanning. Alternating with short-circuit current mapping efficiently provides complementary insight into the highly microstructurally sensitive local and ensemble photovoltaic performance. Furthermore, direct open-circuit voltage mapping is compatible with tomographic AFM, which additionally leverages gradual nanoscale milling by the AFM probe essentially for serial sectioning. The two-dimensional and three-dimensional results for CdTe solar cells during in situ illumination reveal local to mesoscale contributions to PV performance based on the order of magnitude variations in photovoltaic properties with distinct grains, at grain boundaries, and for sub-granular planar defects.
Keywords: cadmium telluride (CdTe); photo-conductive AFM (pcAFM); PV performance; solar cell; tomographic AFM

(untitled) - Kutes, Y.; Aguirre, B. A.; Bosse, J. L.; Cruz-Campa, J. L.; Zubia, D.; Huey, B. D. (Prog. Photovoltaics, 2016)

(untitled) - Leite, M. S.; Abasin, M.; Lezec, H. J.; Gianfrancesco, A.; Talin, A. A.; Zhitenev, N. B. (ACS Nano, 2014)

(untitled) - Sadewasser, S.; Abou-Ras, D.; Azulay, D.; Baier, R.; Balberg, I.; Cahen, D.; Cohen, S.; Gartsman, K.; Ganesan, K.; Kavalakkatt, J.; Li, W.; Millo, O.; et al. (Thin Solid Films, 2011)

(untitled) - Celano, U.; Goux, L.; Belmonte, A.; Opsomer, K.; Franquet, A.; Schulze, A.; Detaverniert, C.; Richard, O.; Bender, H.; Jurczak, M.; Vandervorst, W. (Nano Lett., 2014)

(untitled) - Schulze, A.; Hantschel, T.; Dathe, A.; Eyben, P.; Ke, X.; Vandervorst, W. (Nanotechnology, 2012)

(untitled) - Luria, J.; Kutes, Y.; Moore, A.; Zhang, L.; Stach, E. A.; Huey, B. D. (Nat. Energy, 2016)

(untitled) - Kutes, Y.; Zhou, Y.; Bosse, J. L.; Steffes, J.; Padture, N. P.; Huey, B. D. (Nano Lett., 2016)

(untitled) - Kutes, Y.; Luria, J.; Sun, Y.; Moore, A.; Aguirre, B. A.; Cruz-Campa, J. L.; Aindow, M.; Zubia, D.; Huey, B. D. (Nanotechnology, 2017)

(untitled) - Girish Kumar, S.; Koteswara Rao, K. S. R. (Energy Environ. Sci., 2014)

(untitled) - Li, H.; Liu, X. X.; Lin, Y. S.; Yang, B.; Du, Z. M. (Phys. Chem. Chem. Phys., 2015)

(untitled) - Al-Jassim, M. M.; Yan, Y.; Moutinho, H. R.; Romero, M. J.; Dhere, R. D.; Jones, K. M. (Thin Solid Films, 2001)

(untitled) - Durose, K.; Boyle, D.; Abken, A.; Ottley, C.; Nollet, P.; Degrave, S.; Burgelman, M.; Wendt, R.; Beier, J.; Bonnet, D. (Phys. Status Solidi B, 2002)

(untitled) - Moseley, J.; Metzger, W. K.; Moutinho, H. R.; Paudel, N.; Guthrey, H. L.; Yan, Y.; Ahrenkiel, R. A.; Al-Jassim, M. M. (J. Appl. Phys., 2015)

(untitled) - Poplawsky, J. D.; Paudel, N. R.; Li, C.; Parish, C. M.; Leonard, D.; Yan, Y.; Pennycook, S. J. (Adv. Energy Mater., 2014)

(untitled) - Visoly-Fisher, I.; Cohen, S. R.; Ruzin, A.; Cahen, D. (Adv. Mater., 2004)

(untitled) - Ando, T.; Uchihashi, T.; Fukuma, T. (Prog. Surf. Sci., 2008)

(untitled) - Viani, M. B.; Schäffer, T. E.; Paloczi, G. T.; Pietrasanta, L. I.; Smith, B. L.; Thompson, J. B.; Richter, M.; Rief, M.; Gaub, H. E.; Plaxco, K. W.; Cleland, A. N.; Hansma, H. G.; et al. (Rev. Sci. Instrum., 1999)

(untitled) - Wahlquist, J. A.; DelRio, F. W.; Randolph, M. A.; Aziz, A. H.; Heveran, C. M.; Bryant, S. J.; Neu, C. P.; Ferguson, V. L. (Acta Biomater., 2017)

(untitled) - Ahn, N.; Kwak, K.; Jang, M. S.; Yoon, H.; Lee, B. Y.; Lee, J.-K.; Pikhitsa, P. V.; Byun, J.; Choi, M. (Nat. Commun., 2016)

(untitled) - Kraft, A.; Labusch, L.; Ensslen, T.; Dürr, I.; Bartsch, J.; Glatthaar, M.; Glunz, S.; Reinecke, H. (IEEE J. Photovoltaics, 2015)

(untitled) - Badiee, A.; Ashcroft, I. A.; Wildman, R. D. (Int. J. Adhes. Adhes., 2016)

2011 IEEE Energytech, 2011 - French, R. H.; Murray, M. P.; Lin, W.-C.; Shell, K. A.; Brown, S. A.; Schuetz, M. A.; Davis, R. J. (Solar radiation durability of materials components and systems for Low Concentration Photovoltaic Systems, Cleveland, OH, U.S.A., 25.5.2011-26.5.2011, 2011)

(untitled) - Pern, F. J.; Czanderna, A. W. (Sol. Energy Mater. Sol. Cells, 1992)

(untitled) - Bergmann, V. W.; Weber, S. A. L.; Ramos, F. J.; Nazeeruddin, M. K.; Grätzel, M.; Li, D.; Domanski, A. L.; Lieberwirth, I.; Ahmad, S.; Berger, R. (Nat. Commun., 2014)

(untitled) - Bosse, J. L.; Huey, B. D. (Nanotechnology, 2014)

(untitled) - Huey, B. D.; Kutes, Y.; Longacre, A.; Atamanuk, K.; Luria, J. (Mater. Today)

(untitled) - Visoly-Fisher, I.; Cohen, S. R.; Gartsman, K.; Ruzin, A.; Cahen, D. (Adv. Funct. Mater., 2006)

(untitled) - Li, J. B.; Chawla, V.; Clemens, B. M. (Adv. Mater., 2012)

(untitled) - Galloway, S. A.; Edwards, P. R.; Durose, K. (Sol. Energy Mater. Sol. Cells, 1999)

(untitled) - Green, M. A.; Zhao, J.; Wang, A.; Reece, P. J.; Gal, M. (Nature, 2001)